2014
DOI: 10.1016/j.taap.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of reactive oxygen species in brominated diphenyl ether-47-induced inflammatory cytokine release from human extravillous trophoblasts in vitro

Abstract: Polybrominated diphenyl ethers (PBDEs) are widely used flame retardant compounds. Brominated diphenyl ether (BDE)-47 is one of the most prevalent PBDE congeners found in human breast milk, serum and placenta. Despite the presence of PBDEs in human placenta, effects of PBDEs on placental cell function are poorly understood. The present study investigated BDE-47-induced reactive oxygen species (ROS) formation and its role in BDE-47-stimulated proinflammatory cytokine release in a first trimester human extravillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 67 publications
7
43
0
Order By: Relevance
“…Oxidative stress and the inflammatory reaction interact in a complex way to act in the pathogenesis of lung damage. Studies have demonstrated that ROS are fundamental to oxidative stress and the inflammatory reaction (38,39). The current study demonstrated that NAC and AP application inhibited NAPDH oxidase in the earlier phase and reduced or eliminated ROS production.…”
Section: Discussionsupporting
confidence: 58%
“…Oxidative stress and the inflammatory reaction interact in a complex way to act in the pathogenesis of lung damage. Studies have demonstrated that ROS are fundamental to oxidative stress and the inflammatory reaction (38,39). The current study demonstrated that NAC and AP application inhibited NAPDH oxidase in the earlier phase and reduced or eliminated ROS production.…”
Section: Discussionsupporting
confidence: 58%
“…We also wanted to minimize the potential for artifacts from co-administration, specifically with regards to the presence of serum in the treatment media, which can decrease the bioavailability of lipophilic toxicants including BDE 47 in vitro [65, 66]. Supplementation of the pretreatment exposure media with 5-10% FBS was required for administration of oxEPA/oxDHA to HepG2 cells [37], whereas BDE 47 exposure media utilized in similar in vitro studies are supplemented with very low concentrations of serum (1%) [32, 42], or is serum-free [25, 67]. Thus, co-treatment of cells with oxEPA/oxDHA and BDE 47 should be addressed in future experiments, but was somewhat out of the scope of the current manuscript due to reasons including the aforementioned differences in experimental exposure methods that are required for administering these compounds to cells.…”
Section: Discussionmentioning
confidence: 99%
“…In human [32, 42], fish [29, 30], and rodent cells [26] exposed to BDE 47, oxidative injury is not typically observed below concentrations in the 20-50 μM range. Hence, it is plausible that the antioxidant effects of oxEPA/oxDHA may provide greater protection against, or ameliorate, the toxicity of lower doses of BDE 47 representative of environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations